2009
DOI: 10.5174/tutfd.2009.01534.1
|View full text |Cite
|
Sign up to set email alerts
|

Her-2/neu, Estrogen And Progesterone Receptor Expression In Who Grade I Meningiomas

Abstract: Objectives: Meningiomas are generally benign central nervous system neoplasms, which frequently express progesterone receptor (PR) and rarely express the estrogen receptor (ER). The significance of Her-2/neu expression in meningiomas is unclear. We evaluated the correlation with Her-2/neu, PR, ER expressions and clinicopathologic parameters in World Health Organization (WHO) Grade I meningiomas. Patients and Methods:In total, 53 cases of meningiomas were included in this study. Formaline-fixed, paraffin-embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 15 publications
7
8
1
Order By: Relevance
“…Our finding of more frequent Her-2/neu overexpression in meningothelial meningioma (43% of the classic and 50% of the atypical/anaplastic meningothelial meningiomas) is in accordance with that of Loussouarn et al (2006) and Onak Kandemir et al (2010), who reported more frequent Her-2/ neu overexpression in meningiomas displaying epithelial differentiation, such as meningothelial and secretory histological subtypes. Durand et al (2008), however, have not found such an increased frequency of detection.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our finding of more frequent Her-2/neu overexpression in meningothelial meningioma (43% of the classic and 50% of the atypical/anaplastic meningothelial meningiomas) is in accordance with that of Loussouarn et al (2006) and Onak Kandemir et al (2010), who reported more frequent Her-2/ neu overexpression in meningiomas displaying epithelial differentiation, such as meningothelial and secretory histological subtypes. Durand et al (2008), however, have not found such an increased frequency of detection.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, HER-2 positivity was detected in 13 (34.2%) of the 38 meningioma specimens studied, which is within the wide range of 2.5 to 67.3% reported for Her-2/neu overexpression in meningiomas in the literature (Potti et al, 2004a(Potti et al, , 2004bLoussouarn et al, 2006;Durand et al, 2008;Abdelzaher et al, 2010;Onak Kandemir et al, 2010;Wang et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations